ILUSI KEMISKINAN DAN HIPERREALITAS DALAM FILM POURRIS GÂTÉS (2021) - Safitri, Felisya Dara; Nisa, Azkiya (UI Scholars Hub, 2025)
This study examines the representation of the bourgeois class in the film Pourris Gâtés (2021) by Nicolas Cuche through the theoretical lens of Jean Baudrillard’s concept of hyperreality and Fredric Jameson’s notion of pastiche. The research problem focuses on how Pourris Gâtés depicts the simulated social transformation of the bourgeois class through the illusion of consumerism and hyperreality. The study employs film discourse analysis using both narrative and visual approaches, grounded in media ideology theory, hyperreality, and the consumption of signs. The findings indicate that the main characters undergo a symbolic transformation rather than a structural change. Their identities are constructed through the consumption of luxury goods and social relations that function as status symbols, rather than through labor or authentic experiences. Poverty is aesthetically represented as a moment of learning rather than as an oppressive structural reality. The jobs taken on by the main characters serve as educational stages that remain under the control of privilege. In this way, Pourris Gâtés demonstrates how the bourgeois class sustains itself through a narrative of hyperreality framed within a moralistic aesthetic.